PENANGKAPAN IKAN DENGAN MENGGUNAKAN BAHAN PELEDAK DI WILAYAH PERAIRAN TAKA GARAS MAUMERE - Nur Fitriani; Dyah Setyorini (Fakultas Hukum Universitas Trisakti, 2022)
Illegal fishing often use explosives. The Research’s problem is how the policies regarding fishing gear in Law on Fisheries and the Job Creation Law and how fishing carried out by the Kasdin using explosives in terms of the Law on Fisheries and the Job Creation Law (case study Decision Number 4/Pid.Sus-Prk/2020/PN Mme). The research conducted in normative and descriptive analytical legal research, using secondary data and primary and secondary legal materials. The data is analyzed qualitatively and conclusions drawn using deductive logic method. The conclusion is that the policy related to the prohibition of the use of bombs (chemical explosives) in fishing activities is regulated in Law Number 45 of 2009 concerning Fisheries, Minister of Maritime Affairs and Fisheries Regulation Number 18 of 2021 and Government Regulation Number 27 of 2021 concerning the Implementation of Maritime Affairs and Fishery. Based on the case in Decision Number 4/Pid.Sus-Prk/2020/PNMme, Kasdin violated Article 8 (1) of Law 45/2009 Concerning Fisheries, Article 7 (1) and (2) of Minister of Maritime Affairs and Fisheries Regulation Number 18 of 2021, Article 43 (1) Government Regulation Number 27 of 2021 concerning the Implementation of Maritime Affairs and Fishery and can be categorized as illegal fishing using explosive.